Saving the two-state solution: A transatlantic agenda for the Middle East - Muriel Asseburg; Patrick Müller (Stiftung Wissenschaft und Politik (SWP), 2008)
It is encouraging that - after some seven years of violence and unilateral steps - parties to the Middle East conflict have started to talk to each other again. Results of these talks, however, have so far been sobering, and prospects for conflict settlement in the Middle East are bleak. It is rather unlikely that the so-called Annapolis process will yield an Israeli-Palestinian peace agreement, or even a substantial framework agreement, as envisioned before the end of 2008 - not only because the gaps between the parties remain too wide with regards to the core issues (Jerusalem, refugees, settlements), but also because questions of leadership will be dominating the domestic Israeli, Palestinian and US agendas in the weeks and months to come. Because of the urgency imposed by the rapidly diminishing feasibility of a two-state settlement as well as the imminence of a renewed escalation of violence, the peace process - with a focus on the Israeli-Palestinian track - should be one of the main priorities on the transatlantic agenda
Keywords: 320